Pertanggungjawaban Pidana Pelaku Pembobolan Kartu Kredit Dalam Tindak Pidana Di Bidang Perbankan - Djokdja, Galang Ramadhan; Adam, Sherly; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: There are many cases of fraud with credit cards at banks known as carding, but there is no new legal rule to ensnare the perpetrators so that the judges still use the old rules, namely the Criminal Code. Law enforcement in the banking sector includes regulatory issues in the field of information technology and other aspects are the ability of law enforcement officers, public legal awareness, and infrastructure that supports law enforcement, especially in reviewing criminal liability for perpetrators.Purposes of the Research: Criminal liability for credit card burglary perpetrators in criminal acts in the banking sector. Methods of the Research: The research method used is normative juridical with a problem approach in the form of a statutory approach, a conceptual analysis approach and a case approach. The legal materials used are primary and secondary legal materials. Data collection techniques are carried out through library research and processing techniques and analysis of legal materials through descriptions using qualitative methods.Results of the Research: The results of the study indicate that the criminal law regulation of the crime of carding has been regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and has been formulated in articles 362, 363 and 378 of the Criminal Code. namely about Theft and Fraud. Carding criminal liability can be carried out based on the ability of the perpetrator to be responsible; there is an error in the form of a deliberate act of the perpetrator as proven in accordance with the articles in paragraph; there is no excuse for his actions; and may be subject to sanctions for carding criminals.